Flaubert abandonné. Les mises en musique inachevées des œuvres de Flaubert - Damien Dauge (Flaubert: Revue Critique et Génétique)
The repertoire of musical adaptations of Flaubert’s works does not enjoy large celebrity. However, beside a corpus of musical works which deserve deep investigations, we find great names : Moussorgski, Berlioz, Saint-Saëns, Debussy, Verdi or Rachmaninoff. They all share the following common trait : they ended for giving up the idea of to put Flaubert to music.